Physical fitness parameters in the identification of high-potential sepak takraw players - Rabiu Muazu, Musa; Anwar, P. P. Abdul Majeed; Norlaila Azura, Kosni; Mohamad Razali, Abdullah (Springer, 2020)
This chapter evaluates the significance of different physical fitness parameters towards identifying the fitness level of potential sepak takraw players. The discrimination between high and low-fit players was carried out through hierarchical agglomerative cluster analysis (HACA). In addition, a k-nearest neighbour (k-NN) classifier was developed and evaluated towards its efficacy in classifying the fitness nature of the players. It was demonstrated from the study that the proposed methodology could ascertain the fitness level of the players accurately.